The Model and the Masterpiece (Balzac and his followers) - Sergey N. Zenkin (Studia Litterarum)
Balzac’s short story “The Unknown Masterpiece” (“Le Chef-d’œuvre inconnu”) is one of his most commented works. This essay offers a new reading of the story by correlating the narrative structures of the text with the deforming effect these structures produce on the visual artifact (the painting) featured in “The Unknown Masterpiece.” The analysis takes into consideration the dynamic history of Balzac’s “waving” text undergoing changes with every new authorial revision that obscured the important circumstances of the plot and made the central visual image ambiguous. The latter is stratified as it acquires width instead of depth while the figure it represents protrudes from the smooth surface of the canvas. The close reading of Balzac’s text is followed by the survey of French literary works and films that elaborate, after Balzac, on “the masterpiece and the model” plot. The latter include the works by Théophile Gautier, Goncourt brothers, Émile Zola, and Jacques Rivette.